Study of University Teachers Attitudes to Apply to Research Teaching - Neminska, Rumyana (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2020)
The article traces trends in the development of research teaching in an academic setting. The problem is addressed in two areas: scientific-theoretical and reflexive-empirical. The scientific and theoretical part presents the relation between the quality of training and research training. The reflexive-empirical section presents the results of a study conducted among academic staff at some Bulgarian universities. The survey used to conduct the survey examines areas such as reflection and self-reflection in teaching. Theoretically justified conclusions are presented. The current trends in the research training of students at Bulgarian universities are outlined.